2019
DOI: 10.1093/infdis/jiz275
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Phase Variation in Multiple Outer-Membrane Proteins During Spread of the Hyperinvasive Neisseria meningitidis Serogroup W ST-11 Lineage

Abstract: Background Since 2009, increases in the incidence of invasive meningococcal disease have occurred in the United Kingdom due to a sublineage of the Neisseria meningitidis serogroup W ST-11 clonal complex (hereafter, the “original UK strain”). In 2013, a descendent substrain (hereafter, the “2013 strain”) became the dominant disease-causing variant. Multiple outer-membrane proteins of meningococci are subject to phase-variable switches in expression due to hypermutable simple-sequence repeats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Because pilC mutants express low levels of TFP and are less adhesive, phase variation-mediated switching to OFF of PilC expression may be a means by which meningococci could detach from endothelial cells and reach the bloodstream. Genomic studies have shown that the absence of pilC genes expression was more frequently found in invasive rather than carriage isolates, for example in N. meningitidis serogroup W ST-11 clonal complex strains [71,72]. In vitro, it was shown that following adhesion to epithelial cells, a posttranscriptional modification of the major pilin PilE can occur that destabilizes TFP-dependent contacts and promotes detachment of meningococci from adherent microcolonies [73].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Because pilC mutants express low levels of TFP and are less adhesive, phase variation-mediated switching to OFF of PilC expression may be a means by which meningococci could detach from endothelial cells and reach the bloodstream. Genomic studies have shown that the absence of pilC genes expression was more frequently found in invasive rather than carriage isolates, for example in N. meningitidis serogroup W ST-11 clonal complex strains [71,72]. In vitro, it was shown that following adhesion to epithelial cells, a posttranscriptional modification of the major pilin PilE can occur that destabilizes TFP-dependent contacts and promotes detachment of meningococci from adherent microcolonies [73].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Thus, these data suggest that high rates of transmission between carriers have driven 2013-associated IMD outbreaks, such as the one associated with an international scout convention ( Lucidarme et al, 2016 ), and increasing incident rates of this sub-clone both within the United Kingdom and other countries. We note that these sub-lineages are differentiated by a small number of recombination events and differing lengths of phase-variable repetitive tracts that may be determinants of transmissibility ( Lucidarme et al, 2016 and Green et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Spreading to other European countries where its circulation is already observed as prevalent, the 2013 strain also triggered an international outbreak in 2015 [14][15][16]35]. Genomic analyses have revealed mutations, recombination and different phase variations between the original UK and 2013 strains suggesting possible mechanisms involved in enhanced transmissibility of the 2013 strain [14,36]. We detected one isolate collected in 2018 from the Southeast region related to the 2013 strain, and three isolates collected in 2019 from Midwest and Southeast regions related to the recently described 2015 strain.…”
Section: Discussionmentioning
confidence: 99%